(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation.This research involved designing a prototype expert system that helps patients in diagnosing their diseases and offering them the proper advice; furthermore, the knowledge management used in the expert system is discussed. One of the main objectives of this research was to find a proper language for representing patient’s medical history and current situation into a knowledge base for the expert systems to be able to carry out the consultation effectively. Production rules were used to capture the knowledge.